THE EFFECT OF ACTIVE LEARNING METHODS ON MOTIVATION AND LEARNING ACHIEVEMENT OF ELEMENTARY SCHOOL STUDENTS - Maemunah Maemunah; Ach. Shobri; Muhammad Mahfud; Al-Amin; Mohammad Ahmad Bani Amer (INJOSEDU: International Journal of Social and Education, 2025)
Active learning method is an approach to teaching and learning that emphasises students' direct and active participation in learning activities. Instead of being passive recipients of information, students engage in discussions, simulations, hands-on practice, group projects, and various other forms of interaction designed to stimulate engagement and critical thinking skills. The aim is to increase understanding of the material, motivate students, and ultimately improve learning achievement through a more dynamic and engaging learning experience. The study in this research uses the literature research method. The results of the analysis from various literatures show that active learning methods significantly contribute to increasing students' learning motivation. Students who are directly involved in the learning process tend to have higher interest and enthusiasm, which leads to increased academic commitment. In addition, active learning methods also have a positive impact on students' learning achievement. A deeper understanding of the material, better critical thinking skills, and the ability to apply knowledge in different contexts are some of the resulting benefits. Thus, the implementation of active learning methods in primary schools is proven to be effective in improving students' motivation and learning achievement, making it an important strategy in efforts to improve the quality of primary education.